Manajemen Kurikulum Merdeka Belajar terhadap Penguatan Profil Pelajar Pancasila di SD Negeri 34 Palembang - Imarida Imarida; Yasir Arafat; Syaiful Eddy (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and analyze: (1) the management of the Independent Learning Curriculum in strengthening the Pancasila Student Profile; (2) obstacles in implementing the Independent Learning Curriculum management in strengthening the Pancasila Student Profile; and (3) solutions to overcome these obstacles at Public Elementary School 34 Palembang. The study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, documentation, and literature studies. Data analysis used the Miles and Huberman interactive model which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of the Independent Learning Curriculum plays a significant role in shaping students' character according to the six dimensions of the Pancasila Student Profile, namely faith, devotion to God Almighty and noble character; global diversity; mutual cooperation; independence; critical reasoning; and creativity. Strengthening is carried out through affective, cognitive, and psychomotor aspects which are integrated in learning activities and profile strengthening projects. Obstacles faced include teachers' limited understanding of the concepts and practices of the Independent Learning Curriculum, limited resources and supporting facilities, minimal parental involvement in project-based learning, and difficulties in developing character-based learning evaluations. Proposed solutions include providing ongoing training for educators, strengthening coordination between stakeholders, improving learning facilities, strengthening collaboration between schools and parents, and developing comprehensive and valid assessment instruments to monitor student character development. With these strategies, the implementation of the Independent Learning Curriculum is expected to be more effective and sustainable in realizing the Pancasila Student Profile.